2022
DOI: 10.3390/cancers14071693
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach to Complex Dermal Sarcomas Ensures an Optimal Clinical Outcome

Abstract: Primary dermal sarcomas (PDS) belong to a highly clinically, genetically and pathologically heterogeneous group of rare malignant mesenchymal tumours primarily involving the dermis or the subcutaneous tissue. The tumours are classified according to the mesenchymal tissue from which they originate: dermal connective tissue, smooth muscle or vessels. Clinically, PDS may mimic benign soft tissue lesions such as dermatofibromas, hypertrophic scarring, etc. This may cause substantial diagnostic delay. As a group, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 88 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…The resection was planned based on the clinical appearance, comorbidities, imaging, and pathology reports. The ultimate goal, however, must be clear margins [ 23 ], as incomplete initial resection causes local recurrence [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resection was planned based on the clinical appearance, comorbidities, imaging, and pathology reports. The ultimate goal, however, must be clear margins [ 23 ], as incomplete initial resection causes local recurrence [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, excision with 2 cm margins was recommended for both entities. However, to date, no guidelines for surgical treatment and follow-up have been established [ 23 ]. A recently published probability model based on a systemic review by Jibbe et al found peripheral excision margins of at least 2 cm for AFX and 3 cm for PDS, respectively, to reduce the recurrence rate [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the tissue of origin, these tumors can be classified into dermal, smooth muscle, or vascular lesions, having a vast spectrum regarding their malignant potential. Dermal sarcomas can therefore be divided into dermatofibrosarcoma protuberans (DFSP), atypical fibroxanthoma (AFX), pleomorphic dermal sarcoma (PDS), leiomyosarcoma (LMS), and vascular sarcomas (Kaposi's sarcoma, angiosarcoma) 1 …”
mentioning
confidence: 99%
“…Treatment for Kaposi's sarcoma can be local or systemic. Local therapy includes applications of 30 % prospidin ointment, radiation methods, cryotherapy, injections of chemotherapeutic drugs into the tumor, applications with dinitrochlorobenzene, injections of interferon-alfa into the tumor, and some other methods [7]. Radiation therapy, local chemotherapy, surgical method, cryotherapy with liquid nitrogen, photodynamic therapy, systemic polychemotherapy or palliative monochemotherapy approaches also used [6].…”
mentioning
confidence: 99%